FCR and bevacizumab treatment in patients with relapsed chronic lymphocytic leukemia. Issue 22 (15th July 2014) - Jain, Preetesh; Lee, Hun Ju; Qiao, Wei; Wierda, William; Benjamini, Ohad; Burger, Jan; Ferrajoli, Alessandra; Estrov, Zeev; Kantarjian, Hagop; Keating, Michael; O'Brien, Susan
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with relapsed chronic lymphocytic leukemia (CLL) often achieve response with chemoimmunotherapy but have short remission durations. Studies have shown that patients with CLL have increased angiogenesis in the microenvironment; levels of proangiogenic growth factors such as VEGF and/or angiopoietin‐2 are also elevated. Increased angiogenesis correlates with poor outcome in CLL. Bevacizumab (B) is a humanized monoclonal antibody targeting VEGF‐A. METHODS In this study, we analyzed whether a combination of bevacizumab with fludarabine, cyclophosphamide, and rituximab chemoimmunotherapy (FCR‐B) could improve outcomes in patients with relapsed CLL. Sixty‐two patients were enrolled. The median age of the patients was 60 years (range, 31‐84 years) and 40% had received >1 prior therapy for CLL. Sixty‐one patients were evaluable for toxicity, and 57 were evaluable for response. Six cycles were planned; 36 patients (59%) completed ≥4‐6 cycles of the regimen. RESULTS The overall response rate was 79%, with 13 (23%) complete remissions (CRs), 8 nodular partial remissions (14%), and 24 partial remissions (43%). The median progression‐free survival and overall survival rates were 13.5 and 45 months, respectively. Grade 3 or 4 toxicities included febrile neutropenia (n = 40), infections (n = 21), thrombocytopenia (n = 18) and anemia (n = 9). CONCLUSIONS Results with FCR‐B were similar to those observed with an historical cohort of relapsed patients treated with FCR. Cancer 2014;120:3494–3501. © 2014 American Cancer Society.